Fostering Innovative Work Behavior in Startups: The Interplay between Inclusive Leadership and Psychological Safety. - Madinatul Munawaroh; Muhammad Irsyad Baitussalam (HARAMAIN: Jurnal Manajemen Bisnis, 2025)
In increasingly dynamic and competitive business environments, organizations are required to strengthen their innovation capacity by encouraging employees to generate, promote, and implement new ideas in the workplace. One of the key factors influencing such behavior is leadership, particularly inclusive leadership, which emphasizes openness, accessibility, and appreciation of employee contributions. This study examines the effect of inclusive leadership on innovative work behavior, with psychological safety serving as a mediating variable, in the context of PT. Mifa Bersaudara Aceh. A quantitative explanatory research design was employed, and data were collected from 70 employees using a structured questionnaire with a five-point Likert scale. The data were analyzed using SPSS version 25, including descriptive statistics, validity and reliability testing, classical assumption tests, multiple linear regression, and path analysis. Hypothesis testing was conducted at a 5% significance level. The findings reveal that inclusive leadership has a positive and significant effect on innovative work behavior and also significantly enhances psychological safety. In addition, psychological safety has a positive and significant effect on innovative work behavior and mediates the relationship between inclusive leadership and innovative work behavior. These results indicate that employees are more likely to engage in innovative behavior when they perceive their leaders as open, supportive, and willing to value their contributions, and when they feel safe to express ideas and take interpersonal risks. The study contributes to the literature by clarifying the psychological mechanism through which inclusive leadership fosters innovative work behavior in an organizational context. Practically, the findings suggest that organizations should strengthen inclusive leadership practices and cultivate psychologically safe work environments in order to promote sustainable employee innovation.